Untreated ADHD in Adults Are There Sex Differences in Symptoms, Comorbidity, and Impairment? - Rasmussen, Kirsten; Levander, Sten (Journal of Attention Disorders, 2009)
Objective: To analyze sex differences among adult, never-treated patients referred for central stimulant treatment of ADHD. Method: Data for 600 consecutive patients from northern Norway referred for evaluation by an expert team during 7 years were analyzed. General background information, diagnostic and social history, and symptom profiles were compared between previously never-treated men and women. Results: The sex ratio was skewed. Of the previously untreated patients, more than 20% fell outside society's ordinary vocational activities or social benefit system. Most patients had the combined form, one third the inattentive type, and only 2% the hyperactive/impulsive subtype. Abuse and criminality were more common among men, and affective, eating, and somatization disorders were more common among women. Otherwise few sex differences were found. Conclusion: AD/HD symptom intensity and subtypes did not differ between the sexes and was to age. Symptom intensity was linked with criminality, abuse, and other psychiatric problems, differentially for two sexes. (J. of Att. Dis. 2009; 12(4) 353-360)